58th EASD Annual Meeting from 19 to 23 September 2022, Stockholm, Sweden (Virtual) - Hussein, Wiam I.; Hassanein, Mohammed (Journal of Diabetes and Endocrine Practice, 2022)
The 58th European Association for the Study of Diabetes (EASD) Annual Meeting was held between 19 and 23 September 2022 in Stockholm, Sweden. It was also fully streamlined online. The authors attended the conference, giving a narrative commentary on what they felt were the highlights of the meeting. Several interesting lectures were presented. The ADA-EASD hyperglycemia management consensus was among the landmark presentations. The development of a particular model that could predict severe hypoglycemia risk in people with type 2 diabetes (T2D) was interesting. The remission of T2D data from the ReTUNE analysis backs the “personal fat threshold” concept was very promising. Interestingly, a link between autoimmunity degree and latent autoimmune diabetes in adults' cardiovascular disease (CVD) risk was proposed. A benefit of high-intensity exercise for people with impaired hypoglycemia awareness was demonstrated. The CLOuD, namely, early and sustained closed-loop therapy does not stave off β-cell decline, data were shared. Also, subjective energy levels were shown to predict CV events in T2D. Also, C-peptide may be better than C-reactive protein for predicting CV risk in T2D. Furthermore, a fatty liver index may predict mortality and CVD risk in people with T1D. New data suggest that topical esmolol hydrochloride might aid in the healing of diabetic foot ulcers. Finally, microalbuminuria in pregnancy forecasts adverse outcomes. We hope this short account helps those who did not attend the conference to get a glimpse of the program.
Keywords: cardiovascular; diabetes; diagnosis; hypoglycemia; management